Are the Number of Skilled Workers Running Out in Germany? The (Non)-Consequences of Demographic Change - Alfred Garloff; Rüdiger Wapler (European Regional Science Association (ERSA), 2013)
Two stylised facts of the German labour market are that first, the demand for (high-)skilled labour has been growing rapidly for a number of years and second, the country is facing a particularly strong demographic change with the expected size of the population decreasing rapidly and the average age of the labour force increasing sharply. This has led to a widely discussed fear of ''labour-market shortages' whereby employers simply cannot find ''enough' workers because many more are retiring than younger cohorts are entering. Although there is a simple logic in this argument, it is not beyond doubt, because firstly it is neither clear whether the labour demand side could not counteract this effect nor secondly to which precise situation the description ''shortage' actually refers to. We address both issues from a theoretical and empirical perspective. We find no evidence that a high number of retirees across occupations leads to a higher demand for younger workers. Instead, to a large extent, retirees seem to be ''replaced', if they are replaced at all, by middle-aged cohorts who change occupations.
Keywords: J11; J21; J26; 330; Labour-Market; Demography; Replacement Demand